Sistem Pendukung Keputusan Pemilihan Karyawan Terbaik Pada PT. Garam Menggunakan Metode Weighted Product - Fitriansyah, Yudi; Mardiani, Mardiani (MDP Student Conference, 2025)
PT Garam is one of the largest salt producing companies in Palembang. PT Garam has several obstacles related to the problem of selecting the best employees, namely the criteria for determining the best employees which is currently by determining the best a bsences which are selected by supervisors and admin only. So the best employee appraisal system currently available is considered less effective and unfair. This research aims to build a decision support system for selecting the best employees which can he lp PT Garam in determining the best employees. The system built can manage employee data, criteria data, assess and store assessment data, and calculate assessments using the Weighted Product (WP) method. The system development method uses the Waterfall method. The result of this research is a decision support system that provides a ranking of the best employees based on assessments calculated using the Weighted Product (WP) method .